Effects of Lowering Dialysate Calcium Concentrations on Arterial Stiffness in Patients Undergoing Hemodialysis - Kim, Jwa-Kyung (The Korean Association of Internal Medicine, 2011)
BACKGROUND/AIMS: We assessed changes in hemodynamic and arterial stiffness parameters following reductions of dialysate calcium concentrations in patients undergoing hemodialysis. METHODS: In this prospective study, 20 patients on maintenance hemodialysis (10 females, 10 males) with dialysate calcium concentrations of 1.75 mmol/L were enrolled. At the start of the study, the dialysate calcium level was lowered to 1.50 mmol/L. Serial changes in biochemical, hemodynamic, and arterial stiffness parameters, including pulse wave velocity (PWV) and augmentation index (AIx), were assessed every 2 months for 6 months. We also examined changes in the calcification-inhibitory protein, serum fetuin-A. RESULTS: During the 6-month study period, serum total calcium and ionized calcium decreased consistently (9.5 ± 1.0 to 9.0 ± 0.7, p = 0.002 vs. 1.3 ± 0.1 to 1.1 ± 0.1, p = 0.035). Although no apparent changes in blood pressure were observed, heart-femoral PWW (hf-PWV) and AIx showed significant improvement (p = 0.012, 0.043, respectively). Repeated-measures ANOVA indicated a significant effect of lowering dialysate calcium on hf-PWV (F = 4.58, p = 0.004) and AIx (F = 2.55, p = 0.049). Accompanying the change in serum calcium, serum fetuin-A levels significantly increased (95.8 ± 45.8 pmol/mL at baseline to 124.9 ± 82.2 pmol/mL at 6 months, p = 0.043). CONCLUSIONS: Lowering dialysate calcium concentration significantly improved arterial stiffness parameters, which may have been associated with upregulation of serum fetuin-A.